Pengaruh Brand Image, Promosi dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Pada Pengguna Aplikasi Gojek di Kalangan Gen Z Kota Bandung - Ari Septiana; Widyastuti Nurmalia Utami; Ridlwan Muttaqin (CV. ITTC INDONESIA, 2026)
This research evaluates how brand image, promotional activities, and service quality collectively and individually affect customer satisfaction among Generation Z Gojek users in Bandung. Employing a quantitative methodology with descriptive and verificative frameworks, data were gathered from a sample of 100 participants via purposive sampling. The analytical process involved multiple linear regression executed through SPSS version 27. Empirical evidence demonstrates that brand image, promotion, and service quality simultaneously exert a substantial impact on customer satisfaction, supported by an F-statistic of 286.753. Furthermore, partial analysis indicates that each variable contributes positively and significantly to the outcome. The coefficient of determination (R-Square) was recorded at 0.900, suggesting that 90% of the fluctuations in customer satisfaction are driven by these three integrated factors, while external variables account for the remaining 10%. Notably, brand image was found to be the most influential determinant in shaping user satisfaction within this demographic.